Are fundamentals enough? Explaining price variations in the German day-ahead and intraday power market - Christian Pape; Simon Hagemann; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2015)
European electricity market participants are encouraged to balance intraday deviations from their day-ahead schedules via trades in the intraday market. Together with the increasing produc-tion of variable renewable energy sources, the intraday market is gaining importance. We inves-tigate the explanatory power of a fundamental modeling approach explicitly accounting for must-run operations of combined heat and power plants (CHP) and intraday peculiarities such as a shortened intraday supply stack. The fundamental equilibria between every hour's supply stack and aggregated demand in 2012 and 2013 are modeled to yield hourly price estimates. The major benefits of a fundamental modeling approach are the ability to account for non-linearities in the supply stack and the ability to combine time-varying information consistently. The empirical re-sults show that fundamental modeling explains a considerable share of spot price variance. However, differences between the fundamental and actual prices persist and are explored using regression models. The main differences can be attributed to (avoided) start up-costs, market states and trading behavior.
Keywords: Q41; 330; intraday market for electricity; fundamental price modeling